An optimized Energy Cost Analysis using Fuzzy Logic Control Algorithm for the autonomous Microgrid. Issue 1 (February 2021) - Sreeramulu Mahesh, G.; Gnanatheja Rakesh., V; Dilli Babu, G.; Selvaraj, P.; Ranjit, P.S.
Abstract: In this paper, the significance of Fuzzy Logic Control Algorithm is proposed for determining the effective cost analysis of power generation with respective to the load demand in microgrids. There are many conventional algorithms are developed in the past to evaluate the cost analysis with system constraints, however, they are complex and time consumed. Also, these algorithms are mainly used for conventional systems and are not suitable for microgrids. To overcome these disadvantages, a simple Fuzzy Logic Control Algorithm is used to define the cost analysis effectively. The features of these algorithms are eaisly adapted and incorporated with the objectives of Demand Side Management stratigies in microgrids. In addition, the correlation and an Artificial Bee Colony Optimization technique is proposed between the variables of PV and Wind turbine to obtain the highly accurate power generation samples with respect to the load demands. The analysis of optimization and Fuzzy algorithms are developed using MATLAB Simulation software and the cost analysis are shown for different load variations.